Combined strategies for managing the securities portfolio structure - M. A. Sevodin (Учёные записки Казанского университета: Серия Физико-математические науки)
The possibilities of combining known techniques for optimizing the securities portfolio (SP) structure were studied. A method was introduced that enables the simultaneous use of both passive and active approaches to managing the SP structure. The combined application of these methods is based on techniques for SP diversification and searching for an SP structure that mirrors the SP structure of an index fund. The objective function was modified in order to optimize the SP structure according to the traditional “return–risk” approach. The proposed objective function, along with the security risk, describes the degree to which the desired distribution of SP shares coincides with the distribution generated using an index fund. It was established that the main properties of optimal SPs obtained with the “return–risk” approach also occur in the case under consideration.